2012
DOI: 10.1111/j.1600-9657.2011.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination injuries 3. The risk of pulp necrosis in permanent teeth with extrusion or lateral luxation and concomitant crown fractures without pulp exposure

Abstract: A concomitant crown fracture without pulp exposure significantly increased the risk of PN in teeth with lateral luxation. This risk factor may be used to identify teeth at increased risk of PN following lateral luxation injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 22 publications
3
57
0
5
Order By: Relevance
“…The high frequency of necrosis may be related to the extent of root formation of the teeth included in this research. Some studies showed that the chance of necrosis is greater in teeth with a closed apex (8,(15)(16)(17)(20)(21)(22). Among the types of luxation, intrusion is related to the highest prevalence of pulp necrosis, because this type of This study demonstrated that delay in seeking treatment after trauma can impair the prognosis.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The high frequency of necrosis may be related to the extent of root formation of the teeth included in this research. Some studies showed that the chance of necrosis is greater in teeth with a closed apex (8,(15)(16)(17)(20)(21)(22). Among the types of luxation, intrusion is related to the highest prevalence of pulp necrosis, because this type of This study demonstrated that delay in seeking treatment after trauma can impair the prognosis.…”
Section: Discussionmentioning
confidence: 87%
“…The development of external inflammatory resorption is related to the severity of injury, patient age, stage of root formation and the time of pulp extirpation (15)(16)(17)(18)(19). When the endodontic treatment is delayed, pulpal infection associated with periodontal ligament damage may result in the progression of inflammatory external resorption (15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tal fato evidencia--se porque essas lesões de luxação lateral e extrusiva apresentam um envolvimento endodôntico paralelo que requer intervenção imediata, impedindo a manifestação da reabsorção 14 . Assim, os casos de subluxação apresentaram, neste estudo, um índice de reabsorção maior que os demais traumatismos de maior extensão nos tecidos de sustentação, contrariando o esperado conforme a literatura 7 .…”
Section: Discussionunclassified
“…Istražujući uticaj završenog rasta korena na učesta-lost nekroze došli smo do saznanja da se nekroza češće javlja kod zuba kod kojih je koren u potpunosti formiran a koji su uz frakture istovremeno imali i luksacije, slično zapazanjima drugih istraživača [2,27,28].…”
Section: Diskusijaunclassified